HOW GENDER AND AGE AFFECT TOLERANCE OF COLONOSCOPY. (8th June 2013) - Lai, W; Fung, M; Vatish, J; Pullan, R; Feeney, M
Abstract : Introduction: The aim of a colonoscopist is to perform the procedure safely within a reasonable time limit, and minimise any discomfort/pain caused to their patients. It is therefore useful to recognise factors that can influence patients' tolerance of colonoscopy as part of pre-procedure planning. Aims/Background: We collected data from a local endoscopy unit to evaluate the effect of gender and age on patients' experience of the procedure.Table 1 Method: 354 patients who had bowel cancer screening colonoscopy (and found to have polyps) between January 2010 and December 2011 were identified from the BCSP database (Oracle BI Interactive Dashboards). Endoscopy reports were drawn from Scorpio© reporting system, with the patients' comfort level recorded using the Modified Gloucester Discomfort Score (Figure 1). Results: Male patients had a lower mean comfort score (i.e. better tolerated) than female patients (−0.5, 95% CI −0.47, −0.53) (Table 2 ). This is consistent with the lower mean fentanyl requirement in men compare to women (−6 mcg+/−0.1072). The comfort score also showed a positive correlation when plotted against age, length of procedure and fentanyl requirement (Tables 3 and Figure 1 ). Conclusion: The reason for the less-tolerated colonoscopies for women might be due to previous gynaecological operations and possible longer colon 1 (which predispose to looping). Elderly patients may tolerate the procedure less due to previous abdominal surgery and looping of laxer and longer colons 1. The longer length of procedure suggests a more difficult examination which could contribute to patient discomfort. The amount of Fentanyl used was directly proportional to the comfort score as the endoscopists responded to the patients' discomfort.